Quantifying jumps and external load in netball using VERT inertial measurement units - Brooks, E. R.; Benson, A. C.; Fox, A. S.; Bruce, L. M. (Sports Biomechanics, 2021)
This study assesses the relationship between an inexpensive and an established inertial measurement device for the measurement of movement and jumps in netball. Twenty-five female netballers participated in this study (11 elite and 14 sub-elite). Two inertial measurement devices (Catapult ClearSky T6 and VERT Classic) were worn simultaneously during a training session. The `Kinetic Energy` output provided by the VERT device was compared to the total PlayerLoad collected by the ClearSky T6 device. Automated total jump counts were also compared across devices. A correlation of r = 0.76 (95% confidence interval [CI]; 0.52 to 0.89) was identified between total PlayerLoad and `Kinetic Energy`. Similarly, a correlation of r = 0.81 (95% CI; 0.61 to 0.91) was identified for the relationship between ClearSky T6 jump count and VERT jump count. Mean bias of 1.7 jumps (95% CI; -2.5 to 5.8) with 95% limits of agreement (-17.9 to 21.3) were found when comparing the jump counts between the ClearSky T6 and VERT devices. The correlations found in this study indicate that the VERT devices may be an accessible alternative for sub-elite athletes; however, the wide confidence intervals and limits of agreement warrant caution.